2010
DOI: 10.1007/s10578-010-0194-1
|View full text |Cite
|
Sign up to set email alerts
|

The Separation Anxiety Daily Diary: Child Version: Feasibility and Psychometric Properties

Abstract: This report describes the feasibility and psychometric properties of the child version of the Separation Anxiety Daily Diary (SADD-C) in 125 children (ages 7-14 years) from German-speaking areas of Switzerland. Children with separation anxiety disorder (SAD; n = 58), "other" anxiety disorders (n = 36), and healthy controls (n = 31) recorded the frequency of parent-child separations, along with associated anxiety, thoughts, reactions and subsequent parental responses. Compliance rates were modest, consistent wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…As shown in Table 2, studies examining the QL of children with the following diagnoses of mental disorder were included: attention deficit hyperactivity disorder (ADHD; n = 27) [18; 32-57]; autism spectrum disorder (n = 10) [58][59][60][61][62][63][64][65][66][67]; Gilles de la Tourette syndrome or other tic disorder (n = 6) [68][69][70][71][72][73]; bipolar spectrum disorders (n = 5) [74][75][76][77][78]; enuresis (n = 3) [79][80][81]; separation anxiety disorder and anxiety disorders (n = 3) [82][83][84]; eating disorders (n = 2) [85][86]; major depressive disorder (n = 2) [87][88]; conduct disorder (n = 1) [89]; obsessive-compulsive disorder (n = 1) [24]; and learning disabilities (n = 1) [90]. Five studies included diverse diagnoses of a mental disorder [13-14, 23, 91-92].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Table 2, studies examining the QL of children with the following diagnoses of mental disorder were included: attention deficit hyperactivity disorder (ADHD; n = 27) [18; 32-57]; autism spectrum disorder (n = 10) [58][59][60][61][62][63][64][65][66][67]; Gilles de la Tourette syndrome or other tic disorder (n = 6) [68][69][70][71][72][73]; bipolar spectrum disorders (n = 5) [74][75][76][77][78]; enuresis (n = 3) [79][80][81]; separation anxiety disorder and anxiety disorders (n = 3) [82][83][84]; eating disorders (n = 2) [85][86]; major depressive disorder (n = 2) [87][88]; conduct disorder (n = 1) [89]; obsessive-compulsive disorder (n = 1) [24]; and learning disabilities (n = 1) [90]. Five studies included diverse diagnoses of a mental disorder [13-14, 23, 91-92].…”
Section: Description Of Studiesmentioning
confidence: 99%
“…The reviewed studies were conducted in several countries, including the US (n = 26) [24, 32-33, 37, 43, 45-47, 51, 53, 59-60, 63-64, 67-68, 72-74, 76-78, 86-87, 89, 91]; Germany (n = 6) [40,44,48,54,79,92]; Switzerland (n = 3) [23, 82,84]; the Netherlands (n = 4) [13,38,52,66]; Australia (n = 3) [14,[49][50]; Turkey (n = 3) [41,61,80]; Brazil (n = 2) [39,83]; Spain (n = 2) [36,85]; Italy (n = 2) [70,71]; Taiwan (n = 2) [55][56]; Iran (n = 1) [42]; UK (n = 1) [69]; Norway (n = 1) [35]; Hungary (n = 1) [88]; France (n = 1) [58]; Canada (n = 1) [18]; Japan (n = 1) [81]; Greece (n = 1) [90]; and Mexico (n = 1) [57]. Four studies were conducted in two or more countries [34,62,65,75].…”
Section: Description Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to providing data on compliance, part of the included studies specifically examined the feasibility and validity of the EMA applications that were used (i.e., in ASD [22][23][24], ADHD [25][26][27], mood disorders [28], anxiety disorders [29,30], and psychosis [31]). Based on these studies, we provide an initial review of the feasibility and validity of the EMA measures.…”
Section: Feasibility and Validitymentioning
confidence: 99%
“…It was also noted that two of the three adolescents completed the sampling protocol, with the reason for non-completion being partly related to having to carry around the extra device for the sampling. The modest compliance rates of the mother and child event-based diaries on separations in the two studies in anxiety disorders were discussed in relation to possible forgetfulness, lack of motivation, or an inaccurate reflection of the mothers' and children's experiences in the preset diary options [29,30]. The authors suggested that reminder beeps may improve compliance with this application.…”
Section: Feasibility and Validitymentioning
confidence: 99%